UNDERSTANDING THE IMPACT OF TALENT AND COMPETENCE MANAGEMENT ON EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL COMMITMENT - Nik Haryanti; Imam Junaris; Winarto (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2022)
This study aims to obtain empirical evidence and develop a theory (predictive orientation) of the effect of talent management and competence on performance mediated by organizational commitment at Madrasa Aliyah (MA) Ma'arif Udanawu Blitar. The research approach uses an explanative survey approach. The questionnaire was prepared based on talent management, competence, performance, and organizational commitment. The research data was taken from 30 respondents. Data collection was carried out by using a random sampling technique. In this study, data analysis used the Partial Least Square (PLS) approach using Smart PLS software. PLS is a component or (variance) based structural equation model (SEM). The study shows that talent and competency management affect a person's performance. The better the management of talent and competency, the better the performance will be. When the performance improves, the higher the organizational commitment you have. In addition, the better one's talent management, the higher the organizational commitment.